Noninvasive molecular screening for oral precancer in Fanconi anemia patients - Smetsers, Stephanie E; Velleuer, Eunike; Dietrich, Ralf; Wu, Thijs; Brink, Arjen; Buijze, Marijke; Deeg, Dorly J H; Soulier, Jean; Leemans, C René; Braakhuis, Boudewijn J M; Brakenhoff, Ruud H (Cancer prevention research (Philadelphia, Pa.), 2015)
LOH at chromosome arms 3p, 9p, 11q, and 17p are well-established oncogenetic aberrations in oral precancerous lesions and promising biomarkers to monitor the development of oral cancer. Noninvasive LOH screening of brushed oral cells is a preferable method for precancer detection in patients at increased risk for head and neck squamous cell carcinoma (HNSCC), such as patients with Fanconi anemia. We determined the prevalence of LOH in brushed samples of the oral epithelium of 141 patients with Fanconi anemia and 144 aged subjects, and studied the association between LOH and HNSCC. LOH was present in 14 (9.9%) nontransplanted patients with Fanconi anemia, whereas LOH was not detected in a low-risk group (n = 50, >58 years, nonsmoking/nonalcohol history) and a group with somewhat increased HNSCC risk (n = 94, >58 years, heavy smoking/excessive alcohol use); Fisher exact test, P = 0.023 and P = 0.001, respectively. Most frequent genetic alteration was LOH at 9p. Age was a significant predictor of LOH (OR, 1.13, P = 0.001). Five patients with Fanconi anemia developed HNSCC during the study at a median age of 39.6 years (range, 24.8-53.7). LOH was significantly associated with HNSCC (Fisher exact test, P = 0.000). Unexpectedly, the LOH assay could not be used for transplanted patients with Fanconi anemia because donor DNA in brushed oral epithelium, most likely from donor leukocytes present in the oral cavity, disturbed the analysis. Noninvasive screening using a LOH assay on brushed samples of the oral epithelium has a promising outlook in patients with Fanconi anemia. However, assays need to be adapted in case of stem cell transplantation, because of contaminating donor DNA.